Neuroimaging Findings in Paediatric Patients with Sickle Cell Disease - Abreu, VS (2023)
Sickle cell disease (SCD) is an autosomal recessive haemoglobinopathy, which manifests as multisystem ischaemia and infarction, as well as haemolytic anaemia. The morphological changes of red blood cells (RBCs) that promote ischaemia/infarction as the main multi-systemic manifestation, with associated vasculopathy, may also lead to haemorrhage and fat embolisation. Bone infarctions, whether of the skull or spine, are relatively common with subsequent increased infectious susceptibility. We present a broad spectrum of brain and spine imaging findings of SCD from a level III paediatric hospital in Lisbon, between 2010 and 2022. Our aim is to highlight brain and spine imaging findings from a serial review of multiple patients with SCD and respective neuroimaging characterisation.